Pengaruh Pupuk NPK dan ZPT Organik Terhadap Pertumbuhan dan Hasil Tanaman Mentimun (Cucumis sativus L.) - Nada Anesya; Saptorini Saptorini; Nugraheni Hadiyanti (Universitas Kadiri, 2022)
Increasing cucumber (Cucumis sativus L.) productivity by fertilizing and providing organic growth regulators (ZPT) to meet the nutrients is essential. A study was aimed to determine the interaction effect of the concentration of organic fertilizer NPK and ZPT on the growth and yield of cucumber plants. The research method was a 2-factor Completely Randomized Design (CRD) and replicated three times. The first factor was the concentration of NPK fertilizer which consists of 3 levels: 0.25 l/plant (A1), 0.5 l/plant (A2), and 0.75 l/plant (A2). The second factor was the concentration of organic PGR, which consisted of 3 levels: 0.25 l/plant (N1), 0.5 l/plant (N2), and 0.75 l/plant (N3). Data analysis with analysis of variance continued with the smallest significant difference test (BNT) at 5% level if significantly different. The combination of NPK and organic ZPT fertilizer concentrations significantly affected the number of leaves and plant height. The combination of 0.5 liter NPK fertilizer/plant and 0.5 liter organic ZPT/plant (A2N2) resulted in plant height and the number of leaves of 254.33 cm and 50.33 strands. The combination of NPK and organic ZPT fertilizer concentrations had no significant effect on cucumber fruit's number, length, diameter, and weight. The length and weight of cucumber fruit were highest at the concentration of NPK fertilizer 0.75 l/plant (A3) of 60.09 cm, and 807.31 gr, while at the concentration of organic ZPT 0.75 l/plant (N3) it was 53.90 cm. and 744.64 gr. At a concentration of 0.25 l/plant (A1) of NPK fertilizer, theÂ highest cucumber fruit diameter was 176.68 cm, while at an organic ZPT concentration of 0.25 l/plant (N1) it was 206.05 cm.Peningkatan produktivitas mentimun (Cucumis sativus L.) dengan pemupukan dan pemberian zat pengatur tumbuh organik untuk memenuhi unsur hara yang dibutuhkan tanaman. Penelitian ini bertujuan mengetahui pengaruh interaksi konsentrasi pupuk NPK dan ZPT organik terhadap pertumbuhan dan hasil tanaman mentimun. Metode penelitian yang digunakan adalah Rancangan Acak Lengkap (RAL) 2 faktor dan ulangan sebanyak tiga kali. Faktor pertama yaitu konsentrasi pupuk NPK yang terdiri 3 taraf: 0,25 L/tanaman (A1), 0,5 L/tanaman (A2) dan 0,75 L/tanaman (A2 ). Faktor kedua yaitu konsentrasi ZPT organik yang terdiri 3 taraf: 0,25 L/tanaman (N1), 0,5 L/tanaman (N2), dan 0,75 L/tanaman (N3). Analisis data dengan analisis sidik ragam dan dilanjutkan uji beda nyata terkecil (BNT) taraf 5% apabila berbeda nyata. Kombinasi konsentrasi pupuk NPK dan ZPT organik berpengaruh nyata terhadap jumlah daun dan tinggi tanaman. Kombinasi pupuk NPK 0,5 L/tanaman dan ZPT organik 0,5 L/tanaman (A2N2) menghasilkan tinggi tanaman dan jumlah daun sebesar 254,33 cm dan 50,33 helai. Kombinasi konsentrasi pupuk NPK dan ZPT organik berpengaruh tidak nyata terhadap jumlah, panjang, diameter dan berat buah mentimun. Panjang dan berat buah mentimun tertinggi pada konsentrasi pupuk NPK 0,75 L/tanaman (A3) sebesar 60,09 cm, dan 807,31 gr sedangkan pada konsentrasi ZPT organik 0,75 L/tanaman (N3) sebesar 53,90 cm, dan 744,64 gr. Pada konsentrasi pupuk NPK 0,25 L/tanaman (A1) menghasilkan diameter buah mentimun tertinggi sebesar 176,68 cm sedangkan pada konsentrasi ZPT organik 0,25 L/tanaman (N1) sebesar 206,05 cm.